TANTANGAN DAN PELUANG IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PRAKTEK KERJA LAPANGAN (PKL) DI ERA INDUSTRI 4.0 - KARUBABA, LIDIA; WUTOY, REGINA (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to determine (1) the influence of the industrial era 4.0 on the implementation of street vendors in SMK Negeri 2 Manokwari (2) the effect of strengthening character education on the implementation of street vendors in SMK Negeri 2 Manokwari. (3) Simultaneous influence of character education and industry era on the implementation of street vendors in SMK Negeri 2. Manokwari (4) The challenges of implementing street vendors in SMK Negeri 2 Manokwari. (5) Opportunities for implementing street vendors in SMK Negeri 2 Manokwari. The method used in this study is a quantitative method with quantitative analysis techniques. The results showed that: (1) There was no effect of the industrial era 4.0 on the implementation of street vendors in SMK Negeri 2 Manokwari. (2) There is an effect of strengthening character education on the implementation of street vendors in SMK Negeri 2 Manokwari. The effect of character education and industry era simultaneously on the implementation of street vendors in SMK Negeri 2. Manokwari. (3) The biggest challenge in implementing street vendors in SMK Negeri 2 Manokwari is family economic factors: the importance of strengthening the competency of students at apprenticeship, both in related OPDs, or in existing training bodies